Driving model of land use change on the evolution of carbon stock: a case study of Chongqing, China - Luoshan Zheng; Yangbing Li; Yan Chen; Rong Wang; Shijie Yan; Chunhua Xia; Bing Zhang; Jing’an Shao (Environmental Science and Pollution Research, 2023)

Native ApxIIA secreted by Actinobacillus pleuropneumoniae induces apoptosis in porcine alveolar macrophages dependent on concentration and acylation - Hao Tang; Rong Wang; Siqi Pang; Weiyao Han; Qiuhong Zhang; Qiong Fang; Xiabing Chen; Qi Huang; Dexin Qiu; Rui Zhou; Lu Li (Veterinary Microbiology, 2023)

Carbon quantum dot-induced developmental toxicity in Daphnia magna involves disturbance of symbiotic microorganisms - Yunfeng Ma; Yanhua Liu; Wenling Chen; Fei Li; Ruixin Guo; Rong Ji; Jianqiu Chen (Science of The Total Environment, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Biochar establishing syntrophic partnership between exoelectrogens to facilitate extracellular electron transfer - Gaojun Wang; Lu Chen; Yao Xing; Changxi Sun; Peng Fu; Qian Li; Rong Chen (Science of The Total Environment, 2023)

Association of residential greenness with chronotype among children - Yiting Chen; Yabin Hu; Rong Li; Wenhui Kang; Anda Zhao; Ruoyu Lu; Yong Yin; Shilu Tong; Jiajun Yuan; Shenghui Li (Science of The Total Environment, 2023)

Accelerated aging of lithium-ion batteries: bridging battery aging analysis and operational lifetime prediction - Rui Li; Liying Bao; Lai Chen; Cheng Zha; Jingyang Dong; Nan Qi; Rui Tang; Yun Lu; Meng Wang; Rong Huang; Kang Yan; Yuefeng Su; et al. (Science Bulletin, 2023)

Complete genome analysis of type strain of a novel bacterial family Temperatibacteraceae fam. nov., isolated from surface seawater - Jin-Cheng Rong; Lin-Lin Cui; Xiao-Chen Yang; Mao-Li Yi; Qi Zhao (Marine Genomics, 2023)

Carbon-neutral potential in treatment of N, N-dimethylformamide-containing industrial wastewater: Comparative investigation of energy conservation, carbon reduction and expenditure between UASB and Fenton process - Xinwei Tan; Yuqin Fan; Xinzheng Zhang; Tianwei Hao; Rong Chen; Tao Zhang; Rui Lu; Jianliang Sun; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2023)

Three decades of shade trees improve soil organic carbon pools but not methane uptake in coffee systems - Hao Sun; Fulan Zhang; Syed Turab Raza; Yingmo Zhu; Tao Ye; Li Rong; Zhe Chen (Journal of Environmental Management, 2023)

Effect of geographical origins and pile-fermentation on the multi-element profiles of ripen Pu-erh tea revealed by comprehensive elemental fingerprinting - Jiayi Zhu; Le Chen; Yue Chen; Yuting Rong; Yongwen Jiang; Fuqiao Liu; Qinghua Zhou; Xuehong Wei; Haibo Yuan; Junjie Zhang; Jia Li (Food Control, 2023)

Oligo (ethylene glycol) side chain engineering: An efficient way for boosting the development of green-solvent processable electrochromic devices - Shiyi Li; Qilin Wang; Yuehui Zhai; Zhen Xing; Jundong Zhong; Danming Chao; Xuanbo Zhu; Changru Rong; Zongquan Wu; Zheng Chen (Chemical Engineering Journal, 2023)

Super-stretching and high-performance ionic thermoelectric hydrogels based on carboxylated bacterial cellulose coordination for self-powered sensors - Luzheng Chen; Jiang Lou; Xuhui Rong; Zhuqing Liu; Qijun Ding; Xia Li; Yifei Jiang; Xingxiang Ji; Wenjia Han (Carbohydrate Polymers, 2023)

Chemical constituents of the leaves of Coriaria nepalensis and their chemotaxonomic significance - Min Tan; Xiao-Lan Chen; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Tree species mixture effect on extracellular enzyme kinetics varies with enzyme type and soil depth in subtropical plantations - Xue-Li Jiang; Rong Mao; Zhong-Liang Li; Fu-Sheng Chen; Bin Xu; Jin He; Yu-Xin Huang; Xiang-Min Fang (Plant and Soil, 2023)

Characterization of the Oral Microbiota in Captive Sichuan Golden Snub-nosed Monkeys (Rhinopithecus roxellana) of Different Ages - Rong Chen; Xinyi Liu; Meirong Li; Xiaojuan Xu; Ran Lv; Yuanyuan Chen; Guodong Wang; Changlin Deng; Nan Chen; Ting Jia; Siteng Wang; Guangjin Liu (International Journal of Primatology, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Projected Regional 1.50°C and 2.00°C Warming Threshold-crossing Time Worldwide Using the CMIP6 Models - Yali Meng; Keqin Duan; Wei Shang; Peihong Shi; Shuangshuang Li; Ying Cheng; Rong Chen; Zhaopeng Zhang (Chinese Geographical Science, 2023)

Acquisition parameters and sensitivity analysis affecting the seismic imaging quality of the complex piedmont zone - Hu Zhao; Wen-jun Li; Yong Wu; Zhi-xin Di; Rong-rong Zhao; Wei Chen; Ming-yi Li (Applied Geophysics, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Rhizosphere shapes the associations between protistan predators and bacteria within microbiomes through the deterministic selection on bacterial communities - Yang Yue; Chen Liu; Boting Xu; Yijin Wang; Qihui Lv; Zeyuan Zhou; Rong Li; George A. Kowalchuk; Alexandre Jousset; Qirong Shen; Wu Xiong (Environmental Microbiology, 2023)
The assembly of bacterial communities in the rhizosphere is well‐documented and plays a crucial role in supporting plant performance. However, we have limited knowledge of how plant rhizosphere determines the assembly of protistan predators and whether the potential associations between protistan predators and bacterial communities shift due to rhizosphere selection. To address this, we examined bacterial and protistan taxa from 443 agricultural soil samples including bulk and rhizosphere soils. Our results presented distinct patterns of bacteria and protistan predators in rhizosphere microbiome assembly. Community assembly of protistan predators was determined by a stochastic process in the rhizosphere and the diversity of protistan predators was reduced in the rhizosphere compared to bulk soils, these may be attributed to the indirect impacts from the altered bacterial communities that showed deterministic process assembly in the rhizosphere. Interestingly, we observed that the plant rhizosphere facilitates more close interrelationships between protistan predators and bacterial communities, which might promote a healthy rhizosphere microbial community for plant growth. Overall, our findings indicate that the potential predator–prey relationships within the microbiome, mediated by plant rhizosphere, might contribute to plant performance in agricultural ecosystems.

Mapping high-resolution energy consumption CO2 emissions in China by integrating nighttime lights and point source locations - Mengdi Wang; Rong Li; Meigen Zhang; Liangfu Chen; Fan Zhang; Congwu Huang (Science of The Total Environment, 2023)

Revisiting the South China Sea MORBs: Mg isotope and whole-rock geochemical constraints - Yidi Hong; Tao Wu; Chunfeng Li; Xuegang Chen; Jianggu Lu; Haiou Gu; Rong Xu (Marine Geology, 2023)

A new ground-motion model to predict horizontal PGA, PGV, and spectral acceleration for small-to-moderate earthquakes in the capital circle region of China - Bin Zhang; Xiaojun Li; Yanxiang Yu; Jize Sun; Mianshui Rong; Su Chen (Journal of Asian Earth Sciences, 2023)

Characteristics of landscape and erosion in the Eastern Pamir and their implications for regional fault connections - Yunpeng Wu; Rong Yang; Junqing He; Hanlin Chen; Xiubin Lin; Xuhua Shi; Kaixuan An; Chunyang Li; Shibao Gao; Yaguang Chen (Geomorphology, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Quantum chemical calculation assisted efficient lithium extraction from unconventional oil and gas field brine by β-diketone synergic system - Yunze Zhao; Huifang Xing; Meng Rong; Zheng Li; Xuetuan Wei; Congmei Chen; Huizhou Liu; Liangrong Yang (Desalination, 2023)

Biochar facilitates methanogens evolution by enhancing extracellular electron transfer to boost anaerobic digestion of swine manure under ammonia stress - Gaojun Wang; Peng Fu; Bo Zhang; Ji Zhang; Qiuyi Huang; Gaofei Yao; Qian Li; Mawuli Dzakpasu; Jianfeng Zhang; Yu-You Li; Rong Chen (Bioresource Technology, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Positive relationships between species diversity and genetic diversity on a local scale at Mt. Wu Yi, China - Lei Xie; YueYao Feng; Rong Zhao; Ting Lv; NingJie Wang; Yao Li; Xiao Zheng; ShuiFei Chen; Hui Ding; YanMing Fang (Biodiversity and Conservation, 2023)

Spectral-spatial dynamic graph convolutional network for hyperspectral image classification - Rong Chen; Guanghui Li; Chenglong Dai (Earth Science Informatics, 2023)

Evaluation of the toxicity of clozapine on the freshwater diatom Navicula sp. using the FTIR spectroscopy - Hao-Jun Lei; Xin-Rong Wei; Li-Xia Li; Wei-Jun Sun; Hong-Xing Chen; Dan Li; Lingtian Xie (Chemosphere, 2023)

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Sludge granulation in PN/A enhances nitrogen removal from mainstream anaerobically pretreated wastewater - Zhen Lei; Jingjing Xue; Yongning Feng; Yu-You Li; Zhe Kong; Rong Chen (Science of The Total Environment, 2023)

Synergistic driving effects of risk factors on human brucellosis in Datong City, China: A dynamic perspective from spatial heterogeneity - Li Shen; Ming-hao Sun; Wen-tao Ma; Qing-wu Hu; Chen-xi Zhao; Zu-rong Yang; Cheng-hao Jiang; Zhong-jun Shao; Kun Liu (Science of The Total Environment, 2023)

Cardiovascular effects of wearing respirators against particulate matter: A randomized crossover trial - Xin Meng; Meilin Yan; Meijie Jiang; Xueling Meng; Liang Qi; Xinyan Hu; Ruiwei Xu; Yunxiu Shi; Weiju Li; Shiyi Chen; Tong Zhu; Jing Deng; et al. (Science of The Total Environment, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

In-situ constructing amidoxime groups on metal-free g-C3N4 to enhance chemisorption, light absorption, and carrier separation for efficient photo-assisted uranium(VI) extraction - Kaifu Yu; Yi Li; Xin Cao; Ruixiang Wang; Li Zhou; Linzhen Wu; Ningning He; Jia Lei; Dengjiang Fu; Tao Chen; Rong He; Wenkun Zhu (Journal of Hazardous Materials, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Ferrous ion enhanced Fenton-like degradation of emerging contaminants by sulfidated nanosized zero-valent iron with pH insensitivity - Jia-Qi Chen; Guan-Nan Zhou; Rong-Rong Ding; Qi Li; Han-Qing Zhao; Yang Mu (Journal of Hazardous Materials, 2023)

Inactivation of airborne pathogenic microorganisms by plasma-activated nebulized mist - Li Guo; Pengyu Zhao; Yikang Jia; Zifeng Wang; Min Chen; Hao Zhang; Dingxin Liu; Yong Zhang; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2023)

Selective adsorption and special recognition of roxarsone (ROX) from water by utilizing novel core-shell magnetic molecularly imprinted polymers - Zhipan Wen; Runqiao Chen; Ge Zhang; Shen Li; Yalei Zhang; Xiaoping Liao; Gang Cheng; Rong Chen (Journal of Cleaner Production, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

High-accuracy lunar global brightness-temperature mapping using third-order Fourier fitting and co-kriging interpolation - Yongjiu Feng; Yuze Cao; Xiaohua Tong; Peiqi Wu; Shurui Chen; Pengshuo Li; Mengrong Xi; Zhenkun Lei; Rong Wang (Icarus, 2023)

Icariin inhibits hypertrophy by regulation of GPER1 and CaMKII/HDAC4/MEF2C signaling crosstalk in ovariectomized mice - Wenxia Zhao; Xiaoli Shan; Xueqin Li; Shuang Lu; Lei Xia; Huihua Chen; Chen Zhang; Wei Guo; Ming Xu; Rong Lu; Pei Zhao (Chemico-Biological Interactions, 2023)

Sensitive temperature changes on the Tibetan Plateau in response to global warming - Yali Meng; Keqin Duan; Peihong Shi; Wei Shang; Shuangshuang Li; Ying Cheng; Li Xing; Rong Chen; Jinping He (Atmospheric Research, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Neuroglobin Facilitates Neuronal Oxygenation through Tropic Migration under Hypoxia or Anemia in Rat: How Does the Brain Breathe? - Chun-Yang Li; Hai-Feng Jiang; Li Li; Xiao-Jing Lai; Qian-Rong Liu; Shang-Bin Yu; Cheng-La Yi; Xiao-Qian Chen (Neuroscience Bulletin, 2023)

Genetic parameter estimates for estrus duration and urinary hormone levels in captive female giant pandas - He Huang; Shiyi Chen; Yongyou Feng; Zongjin Ye; Rong Hou; Yuliang Liu; Li Luo; Xiangming Huang; Kongju Wu; James Ayala; Kailai Cai; Jingchao Lan (Mammalian Biology, 2023)

Contrasting effects of rice husk and its biochar on N2O emissions and nitrogen leaching from Lei bamboo soils under subtropical conditions - Rong Zhou; Zhe Chen; Ali EI-Naggar; Linlin Tian; Chengpeng Huang; Zhen Zhang; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Biology and Fertility of Soils, 2023)

Differences in particulate matter retention and leaf microstructures of 10 plants in different urban environments in Lanzhou City - Rong Huang; Qing Tian; Yue Zhang; Zhini Chen; Yonghua Wu; Zizhen Li; Zebin Wen (Environmental Science and Pollution Research, 2023)

Identification of novel serum protein biomarkers in the context of 3P medicine for intravenous leiomyomatosis: a data-independent acquisition mass spectrometry-based proteomics study - Zhitong Ge; Penghui Feng; Zijuan Zhang; Zhiyong Liang; Rong Chen; Jianchu Li (EPMA Journal, 2023)

Concentrations and homologue patterns of SCCPs and MCCPs in the serum of the general population of adults in Hangzhou, China - Jianyun Zhang; Hanyu Liao; Yanhong Chen; Xue Li; Rong Chen; Shufen Han; Shuren Liu; Shanshan Yin (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Characterization of elastoplastic behavior and retrieval of active zone depth for expansive soil slopes in the middle-route channel head of the South-to-North Water Diversion Project, China, using InSAR time series - Ziyuan Li; Jun Hu; Xing Zhang; Wanji Zheng; Wenqing Wu; Yaogang Chen; Pinjun Tang; Rong Gui (Remote Sensing of Environment, 2023)

Multiple insights into lignin-mediated cadmium detoxification in rice (Oryza sativa) - Qin Dong; Yingjie Wu; Bing Li; Xi Chen; Lu Peng; Zulfiqar Ali Sahito; Huanxiu Li; Yulan Chen; Qi Tao; Qiang Xu; Rong Huang; Youlin Luo; et al. (Journal of Hazardous Materials, 2023)

Clinical poisoning events involving yunaconitine may be highly correlated with metabolism-based interactions: A critical role of CYP3A4 - Xiaocui Li; Yu Fu; Huawei Qiu; Xueyu Xu; Tingting Lin; Weiqing Hou; Weiying Chen; Rong Zhang; Zhongqiu Liu; Lijun Zhu (Food and Chemical Toxicology, 2023)

Multiscale CFD modelling for conformal atomic layer deposition in high aspect ratio nanostructures - Yuanxiao Chen; Zoushuang Li; Ziao Dai; Fan Yang; Yanwei Wen; Bin Shan; Rong Chen (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Electrospun polyvinyl alcohol-chitosan dressing stimulates infected diabetic wound healing with combined reactive oxygen species scavenging and antibacterial abilities - Haibing Liu; Rong Chen; Pinkai Wang; Jinlang Fu; Zinan Tang; Jiajun Xie; Yanhong Ning; Jian Gao; Qiang Zhong; Xin Pan; Ding Wang; Mingyuan Lei; et al. (Carbohydrate Polymers, 2023)

Performance and mechanism of different pretreatment methods for inoculated sludge in biohydrogen production - Wei-xin Cheng; Ling-ling Wang; Yun Xu; Si-jia Li; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2023)

Prediction of daily PM2.5 and ozone based on high-density weather stations in China: Nonlinear effects of meteorology, human and ecosystem health risks - Lili Wang; Boya Liu; Rong Li; Xingfeng Chen; Lili Liu; Xiao Tang; Jingda Liu; Zhiheng Liao; Jinyuan Xin; Yuesi Wang; Bo Hu (Atmospheric Research, 2023)

Correction to: Increasing net ecosystem carbon budget and mitigating global warming potential with improved irrigation and nitrogen fertilization management of a spring wheat farmland system in arid Northwest China - Yue Li; Rong Wang; Zhijun Chen; Yunwu Xiong; Quanzhong Huang; Guanhua Huang (Plant and Soil, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Activation of Pgk1 Results in Reduced Protein Aggregation in Diverse Neurodegenerative Conditions - Hao Chen; Yajie Li; Jingwen Gao; Qi Cheng; Lei Liu; Rong Cai (Molecular Neurobiology, 2023)

Hyperglycemia symptom amelioration by Ascophyllum nodosum polysaccharides in mice with type 2 diabetes - Ligen Chen; Liang Shen; Lingyun Zhu; Fengwei Li; Xiaodong Ge; Xiujuan Xia; Hongwei Yan; Tingting Liu; Wei Xu; Rong Shao (Algal Research, 2023)

Geochemical behaviors of uranium and thorium during weathering and pedogenesis of carbonate rock: constraint from their speciation - Qiang Ma; Bing-jie Zhou; Zhi-gang Feng; Xiao-long Wang; Rong Chen; Pei-shan Li; Chong Huang (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Dietary selenium requirement for on-growing grass carp, Ctenopharyngodon idellus - Feifei Chen; Ziyi Zhang; Li Wang; Haodong Yu; Xuezhen Zhang; Keming Rong (Aquaculture, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Increasing net ecosystem carbon budget and mitigating global warming potential with improved irrigation and nitrogen fertilization management of a spring wheat farmland system in arid Northwest China - Yue Li; Rong Wang; Zhijun Chen; Yunwu Xiong; Quanzhong Huang; Guanhua Huang (Plant and Soil, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

High-resolution forest age mapping based on forest height maps derived from GEDI and ICESat-2 space-borne lidar data - Xudong Lin; Rong Shang; Jing M. Chen; Guoshuai Zhao; Xiaoping Zhang; Yiping Huang; Guirui Yu; Nianpeng He; Li Xu; Wenzhe Jiao (Agricultural and Forest Meteorology, 2023)

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Hydroclimate changes since the last glacial maximum from sedimentary biomarkers in a crater lake in the Great Khingan Mountains, Northeast China - Weiwei Sun; Enlou Zhang; Enfeng Liu; Yang You; Jingjing Li; Zhenyu Ni; Xianqiang Meng; Wenfang Zhang; Rong Chen (Quaternary Science Reviews, 2023)

An improved RRT algorithm based on prior AIS information and DP compression for ship path planning - Qiyong Gu; Rong Zhen; Jialun Liu; Chen Li (Ocean Engineering, 2023)

Individual and joint association of phenols, parabens, and phthalates with childhood lung function: Exploring the mediating role of peripheral immune responses - Yiting Chen; Jinhong Wu; Rong Li; Wenhui Kang; Anda Zhao; Yong Yin; Shilu Tong; Jiajun Yuan; Shenghui Li (Journal of Hazardous Materials, 2023)

Identification and characterization of goat milk key flavor compounds and their precursors in electron beam irradiation and pasteurization on raw - Chunlu Wen; Ya Chen; Madina; Linlu Zhang; Yue Peng; Bai Rong; Linjie Xi; Shengqi Jiang; Jiangtao Yu; Junqing Bai; Niu Wei; Li Kui; et al. (Innovative Food Science & Emerging Technologies, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

A study of the lipid profile of Coix seeds from four areas based on untargeted lipidomics combined with multivariate algorithms to enable tracing of their origin - Peng Chen; Yabo Shi; Xiaoyan Xiao; Rong Xue; Yu Li; Lin Li; Chunqin Mao; Tulin Lu; Conglong Xu (Food Research International, 2023)

Characterizations of food-derived ellagic acid-Undaria pinnatifida polysaccharides solid dispersion and its benefits on solubility, dispersity and biotransformation of ellagic acid - Zhao-Rong Li; Rui-Bo Jia; Xueyuan Cai; Donghui Luo; Chong Chen; Mouming Zhao (Food Chemistry, 2023)

Corrigendum to “Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels” [Food Hydrocolloids 139 (2023) 108527] - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Amorphous biomineral-reinforced hydrogels with dramatically enhanced toughness for strain sensing - Jia-hua Liu; Zhengyi Mao; Yuhan Chen; Yunchen Long; Haikun Wu; Junda Shen; Rong Zhang; Oscar W.H. Yeung; Binbin Zhou; Chunyi Zhi; Jian Lu; Yang Yang Li (Chemical Engineering Journal, 2023)

Spatiotemporal characteristics of extreme hydrometeorological events and its potential influencing factors in the Huaihe River Basin, China - Rong Gan; Dandan Li; Changzheng Chen; Feng Yang; Xinyu Zhang; Xiaomin Guo (Stochastic Environmental Research and Risk Assessment, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

Segmentation of retinal vessels in fundus images based on U-Net with self-calibrated convolutions and spatial attention modules - YiBiao Rong; Yu Xiong; Chong Li; Ying Chen; Peiwei Wei; Chuliang Wei; Zhun Fan (Medical & Biological Engineering & Computing, 2023)

QTL mapping and candidate gene prediction for the sensitivity of flag leaf angle to exogenous GA3 in rice (Oryza sativa L.) - Yulong Li; Siqi Chen; Xing Wang; Ze Liu; Xiyong Zhao; Weiwen Li; Zhuannan Chu; Delin Hong; Songbai Rong (Euphytica, 2023)

Independent and combined associations of multiple-heavy-metal exposure with lung function: a population-based study in US children - Yiting Chen; Anda Zhao; Rong Li; Wenhui Kang; Jinhong Wu; Yong Yin; Shilu Tong; Shenghui Li; Jianyu Chen (Environmental Geochemistry and Health, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

Dietary exposure risk assessment of pyrethroids in fruits and vegetables: a national scale investigation - Qianqian Li; Bei Li; Dawei Chen; Rong Zhang; Shuyan Liu; Shupeng Yang; Yi Li; Jianxun Li (Environmental Science and Pollution Research, 2023)

Recent advances of nanomaterial-based optical sensor for the detection of benzimidazole fungicides in food: a review - Md Mehedi Hassan; Yi Xu; Muhammad Zareef; Huanhuan Li; Yawen Rong; Quansheng Chen (Critical Reviews in Food Science and Nutrition, 2023)

Aquatic photolysis of high-risk chemicals of emerging concern from secondary effluent mediated by sunlight irradiation for ecological safety and the enhanced methods - Danyang Li; Xiaoyan Y. Ma; Shiying Zhang; Yongkun K. Wang; Yingnan Han; Rong Chen; Xiaochang C. Wang; Huu Hao Ngo (Water Research, 2023)

Multi-chambers of pilot-scale reactor enhanced partial nitritation performance - Kuo Zhang; Xinjue Li; Maofu Chen; Jingqi Sun; Kaiyu Rong; Sitong Liu (Science of The Total Environment, 2023)

Driving effects of land use and landscape pattern on different spontaneous plant life forms along urban river corridors in a fast-growing city - Xiaopeng Li; Yilun Li; Sining Zhang; Rong Lin; Mingkun Chen; Li Feng (Science of The Total Environment, 2023)

SRSF1 is crucial for male meiosis through alternative splicing during homologous pairing and synapsis in mice - Longjie Sun; Juan Chen; Rong Ye; Zheng Lv; Xuexue Chen; Xiaomei Xie; Yuheng Li; Chaofan Wang; Pengbo Lv; Lu Yan; Shuang Tian; Xiaohong Yao; et al. (Science Bulletin, 2023)

Anti-inflammatory cembrane-based diterpenoids isolated from the octocoral Sinularia querciformis - Te-An Kung; Lo-Yun Chen; Chia-Ying Li; Bo-Rong Peng; Tsong-Long Hwang; Ping-Jyun Sung; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2023)

The impact of inorganic ions on the solar photolysis of chlorinated dissolved organic matter from different sources: Spectral characteristics, disinfection byproducts, and biotoxicities - Yali An; Xiaoyan Y. Ma; Wenfeng Chen; Wei Li; Siyan Yang; Rong Chen; Xiaochang C. Wang (Journal of Hazardous Materials, 2023)

Mechanistic insights into effect of in-situ microplastics on heavy metals leaching behavior from its dyeing sludge incineration bottom ash - Xiaoao Shi; Hao Rong; Jinping Li; Yifan Zhao; Lu Ren; Si Chen; Jingxin Liu; Meng Mei; Yongjie Xue; Teng Wang (Journal of Environmental Chemical Engineering, 2023)

Ag@Bi5O7I nanoparticles deposited on Bi(OH)3 nanosheets for boosting photocatalytic antibacterial activity under visible light irradiation - Qinghan Chen; Li Wang; Dehui He; Bo Xiao; Xia Ran; Rong Li; Hong Xu; Jian Feng (Journal of Environmental Chemical Engineering, 2023)

Mechanism of polycyclic aromatic hydrocarbons degradation in the rhizosphere of Phragmites australis: Organic acid co-metabolism, iron-driven, and microbial response - Ni-chen Zhang; Dan A; Yuan-qing Chao; Hai-Yan Li; Charles Li; Qing-qi Lin; Ya-ying Li; Rong-liang Qiu (Environmental Pollution, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Receiver function imaging of dense seismic array and deep dynamic mechanism beneath the eastern South China - Rubing Han; Dinghui Yang; Qiusheng Li; Rong Huang; Hongshuang Zhang; Jiangtao Li; Hao Chen; Zhuo Ye; Wei Fu (Science China Earth Sciences, 2023)

Molecular Hydrogen Mediates Neurorestorative Effects After Stroke in Diabetic Rats: the TLR4/NF-κB Inflammatory Pathway - Wan-Chao Yang; Ting-ting Li; Qiang Wan; Xin Zhang; Li-Ying Sun; Yu-Rong Zhang; Pei-Chen Lai; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)
Diabetes is an independent risk factor for stroke and amplifies inflammation. Diabetic stroke is associated with a higher risk of death and worse neural function. The identification of effective anti-inflammatory molecules with translational advantages is particularly important to promote perioperative neurorestorative effects. Applying molecular hydrogen, we measured blood glucose levels before and after middle cerebral artery occlusion (MCAO), 48-h cerebral oedema and infarct volumes, as well as 28-day weight, survival and neurological function. We also measured the levels of TLR4, NF-κB p65, phosphorylated NF-κB p65, catecholamines, acetylcholine and inflammatory factors. All measurements comprehensively showed the positive effect and translational advantage of molecular hydrogen on diabetic stroke. Molecular hydrogen improved the weight, survival and long-term neurological function of rats with diabetic stroke and alleviated changes in blood glucose levels before and after middle cerebral artery occlusion (MCAO), but no difference in circadian rhythm was observed. Molecular hydrogen inhibited the phosphorylation of NF-κB and significantly reduced inflammation. Molecular hydrogen mediates neurorestorative effects after stroke in diabetic rats. The effect is independent of circadian rhythms, indicating translational advantages. The molecular mechanism is related to the TLR4/NF-κB pathway and inflammation. Graphical abstract Molecular hydrogen (H 2 ) affects outcomes of ischemic stroke with diabetes mellitus (DM).

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Molecular detection and characterization of three novel parvoviruses belonging to two different subfamilies in zoo birds - Yan Wang; Yijie Sun; Xin Li; Rong Chen; Wang Li; Li Ji; Qifan Zhao; Likai Ji; Shixing Yang; Wen Zhang (Archives of Virology, 2023)

Secukinumab plays a synergistic role with starvation therapy in promoting autophagic cell death of hepatocellular carcinoma via inhibiting IL-17A-increased BCL2 level - Rong Tang; Linmei Zheng; Jinfang Zheng; Jincai Wu; Pingping Chen; Jiacheng Chen; Dafeng Xu; Yongchao Zeng; Qijin Li; Zhensheng Zhang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Corrigendum to ’ Biochar enhances the biotransformation of organic micropollutants (OMPs) in an anaerobic membrane bioreactor treating sewage’ [Water Research 223 (2022) 118974] - Zhen Lei; Shixin Zhang; Lianxu Wang; Qian Li; Yu-You Li; Xiaochang C. Wang; Rong Chen (Water Research, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Exposure to real-ambient particulate matter induced vascular hypertrophy through activation of PDGFRβ - Hongxu Bao; Benying Li; Qing You; Xinyu Dun; Zhen Zhang; Yanan Liang; Yahui Li; Qixiao Jiang; Rong Zhang; Rui Chen; Wen Chen; Yuxin Zheng; et al. (Journal of Hazardous Materials, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

Biochar enhanced organic matter transformation during pig manure composting: Roles of the cellulase activity and fungal community - Yanan Yin; Mengtong Li; Xiaohui Tao; Chao Yang; Wenrong Zhang; Haichao Li; Yucong Zheng; Xiaochang Wang; Rong Chen (Journal of Environmental Management, 2023)

Phytoplankton community changes in a coastal upwelling system during the last century - Peng Peng; Rong Bi; Julian P. Sachs; Jie Shi; Yifei Luo; Weifang Chen; Chih-An Huh; Meng Yu; Yali Cao; Yaoyao Wang; Zhong Cao; Xiaohan Bao; et al. (Global and Planetary Change, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Air-water interfacial properties and quantitative description of pea protein isolate-Tween 20 - Qian Shen; Wei Zheng; Fei Han; Jingnan Zuo; Jun Dai; Cuie Tang; Rong Song; Bin Li; Yijie Chen (Food Hydrocolloids, 2023)

Linear and nonlinear interface rheological behaviors and structural properties of pea protein (vicilin, legumin, albumin) - Qian Shen; Jing Li; Xiaojun Shen; Xinyu Zhu; Jun Dai; Cuie Tang; Rong Song; Bin Li; Yijie Chen (Food Hydrocolloids, 2023)

Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Molecular characterization and antimicrobial activity of NK-lysin in black scraper (Thamnaconus modestus) - Mei-Yi Liu; Yi-Rong Zhang; Jian-Hua Zhang; Liang Miao; Yun-Fei Dang; Chen-Jie Fei; Chang-Hong Li; Jiong Chen (Fish & Shellfish Immunology, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

A region-scale decoupling effort analysis of carbon dioxide emissions from the perspective of electric power industry: a case study of China - Rong Li; Zi Chen; Junyong Xiang (Environment, Development and Sustainability, 2023)

The application of 3D printing technology on starch-based product: A review - Liyuan Rong; Xianxiang Chen; Mingyue Shen; Jun Yang; Xin Qi; Yulin Li; Jianhua Xie (Trends in Food Science & Technology, 2023)

Methane emission under straw return is mitigated by tillage types depending on crop growth stages in a wheat-rotated rice farming system - Zheng-Rong Kan; Yifan Li; Xinyu Yang; Silong Zhai; Yi Meng; Chaofan Xu; Jianying Qi; Feng-Min Li; Changqing Chen; Haishui Yang (Soil and Tillage Research, 2023)

Real-ambient particulate matter exposure-induced FGFR1 methylation contributes to cardiac dysfunction via lipid metabolism disruption - Benying Li; Yanan Liang; Hongxu Bao; Daochuan Li; Ying Zhang; Xinyu Dun; Zijian Xu; Andong Ji; Zhen Zhang; Yahui Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

Karst-ecological changes during the middle and late Holocene in Southwest China revealed by δ18O and δ13C records in a stalagmite - Rong Duan; Ting-Yong Li; Jun-Yun Li; Christoph Spötl; Hong-Chun Li; Hai-Bo Wang; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Jing-Li Zhou; Chao-Jun Chen; Tsai-Luen Yu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

TiO2/g-C3N4 photoanode prepared with polydopamine inspiration for photocatalytic fuel cells towards simultaneous wastewater treatment and electricity generation - Yuxin Liu; Lin Chen; Jinwang Li; Rong Chen; Xun Zhu; Dingding Ye; Yang Yang; Qiang Liao (Journal of Water Process Engineering, 2023)

Does carbon emission trading mitigate firm's default risk? Evidence from China - Qingjun Zhang; Sulan Zhang; Rong Chen; Jing Li (Journal of Cleaner Production, 2023)

Generation of low-cadmium rice germplasms via knockout of OsLCD using CRISPR/Cas9 - Huamei Chen; Rong Ye; Ying Liang; Shuchang Zhang; Xiulian Liu; Chongjun Sun; Fangbai Li; Jicai Yi (Journal of Environmental Sciences, 2023)

Disinfection byproducts in indoor swimming pool water: Detection and human lifetime health risk assessment - Di Zhang; Shengkun Dong; Li Chen; Rong Xiao; Wenhai Chu (Journal of Environmental Sciences, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

Chemical constituents from the root bark of Morus alba and their chemotaxonomic significance - Xiao-Cong Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

The mutual interactions among ozone, fine particulate matter, and carbon dioxide on summer monsoon climate in East Asia - Danyang Ma; Tijian Wang; Beiyao Xu; Rong Song; Libo Gao; Huimin Chen; Xuejuan Ren; Shu Li; Bingliang Zhuang; Mengmeng Li; Min Xie; Eri Saikawa (Atmospheric Environment, 2023)

The inhibition mechanism and death mode of Microcystis aeruginosa induced by the continuous pressure of artemisinin sustained-release microspheres (ASMs) - Cunhao Du; Lixiao Ni; Jakpa Wizi; Wenlu Sang; Shiyi Rong; Xianglan Li; Chu Xu; Yan Li; Xuqing Chen; Shiyin Li (Algal Research, 2023)

Whole-genome sequencing reveals putative underlying mechanisms of biocontrol capability of IBFCBF-5 - Chen Luo; Ai-rong Shen; Ye-song Ren; Yang Zhai; Yi Cheng; Jianping Xu; Lin Wei; Ji-lie Li; Liang-bin Zeng (Acta Physiologiae Plantarum, 2023)

Nogo-A Mediated Endoplasmic Reticulum Stress During Myocardial Ischemic-Reperfusion Injury in Diabetic Rats - Yonghong Xiong; Yan Leng; Wei Li; Wenyuan Li; Hao Tian; Jie Tao; Rong Chen; Zhongyuan Xia (Cardiovascular Toxicology, 2023)

Preliminary Investigation on Marine Radar Oil Spill Monitoring Method Using YOLO Model - Bo Li; Jin Xu; Xinxiang Pan; Rong Chen; Long Ma; Jianchuan Yin; Zhiqiang Liao; Lilin Chu; Zhiqiang Zhao; Jingjing Lian; Haixia Wang (Journal of Marine Science and Engineering, 2023)
Due to the recent rapid growth of ocean oil development and transportation, the offshore oil spill risk accident probability has increased unevenly. The marine oil spill poses a great threat to the development of coastal cities. Therefore, effective and reliable technologies must be used to monitor oil spills to minimize disaster losses. Based on YOLO deep learning network, an automatic oil spill detection method was proposed. The experimental data preprocessing operations include noise reduction, gray adjustment, and local contrast enhancement. Then, real and synthetically generated marine radar oil spill images were used to make slice samples for training the model in the YOLOv5 network. The detection model can identify the effective oil spill monitoring region. Finally, an adaptive threshold was applied to extract the oil slicks in the effective oil spill monitoring regions. The YOLOv5 detection model generated had the advantage of high efficiency compared with existing methods. The offshore oil spill detection method proposed can support real-time and effective data for routine patrol inspection and accident emergency response.

The phosphorus harvest from low-temperature mainstream wastewater through iron phosphate crystallization in a pilot-scale partial nitritation/anammox reactor - Yan Guo; Eli Hendrik Sanjaya; Tianjie Wang; Chao Rong; Zibin Luo; Yi Xue; Hong Chen; Yu-You Li (Science of The Total Environment, 2023)

Global photosynthetic capacity of C3 biomes retrieved from solar-induced chlorophyll fluorescence and leaf chlorophyll content - Yihong Liu; Jing M. Chen; Liming He; Rong Wang; Nicholas G. Smith; Trevor F. Keenan; Cheryl Rogers; Wenyu Li; Jiye Leng (Remote Sensing of Environment, 2023)

Olefin-linked cationic covalent organic frameworks for efficient extraction of ReO4−/99TcO4− - Wei-Rong Cui; Wei Xu; Yi-Ru Chen; Kai Liu; Wei-Bin Qiu; Yibao Li; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Estimating divergent forest carbon stocks and sinks via a knife set approach - Shitephen Wang; Keito Kobayashi; Satoru Takanashi; Chiung-Pin Liu; Dian-Rong Li; San-Wen Chen; Yu-Ting Cheng; Kai Moriguchi; Masako Dannoura (Journal of Environmental Management, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Synergistic and antagonistic effects of preharvest salicylic acid and postharvest 1-methylcyclopropene treatments on the storage quality of apricot - Changchang Liang; Xinzhi Cui; Chanchan Sun; Sunxiang Ye; Ningxin Huang; Rong Chen; Aidi Zhang; Yanqing Yang; Hansheng Gong; Shuyang Sun; Fengjun Guo; Xinguang Fan; et al. (Food Chemistry, 2023)

Constructing redox-active 3D covalent organic frameworks with high-affinity hexameric binding sites for enhanced uranium capture - Yi-Ru Chen; Xiu Wang; Wei Xu; Kai Liu; Wei-Bin Qiu; Yongquan Wu; Yibao Li; Wei-Rong Cui (Chemical Engineering Journal, 2023)

Dual-functional electrostatic self-assembly nanoparticles enable suppressed defects and improved charge transport in perovskite optoelectronic devices - Hu Zhang; Pengfei Xu; Zhiliang Chen; Hengkai Zhang; Wenlong Shao; Yanhui Li; Jianfeng Yao; Da Rong; Duanwangde Liu; Liangpan Yang; Siliang Wang; Pengbin Gui; et al. (Chemical Engineering Journal, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Radon exhalation from cement-based materials under accelerated carbonation - Rong Yang; Jie Wang; Xiaowen Zhang; Jie Li; Mianbiao Chen (Environmental Science and Pollution Research, 2023)

Mechanism of YY1 mediating autophagy dependent ferroptosis in PM2.5 induced cardiac fibrosis - Huaifang Hu; Lipeng Li; Huaxing Zhang; Yaling Zhang; Qingping Liu; Meiyu Chen; Jie Ning; Yaxian Pang; Wentao Hu; Yujie Niu; Rong Zhang (Chemosphere, 2023)

Density estimation method of mature wheat based on point cloud segmentation and clustering - Rong Zou; Yu Zhang; Jin Chen; Jinyan Li; Wenjie Dai; Senlin Mu (Computers and Electronics in Agriculture, 2023)

Exosome proteomics study of the effects of traditional cigarettes and electronic cigarettes on human bronchial epithelial cells - Weiling Wang; Rong Zeng; Min Liu; Mulan Chen; Shiqin Wei; Bowen Li; Suhong Yu (Toxicology in Vitro, 2023)

Straw incorporation interacting with earthworms mitigates N2O emissions from upland soil in a rice-wheat rotation system - Zheng-Rong Kan; Jiajia Zhou; Feng-Min Li; Mohamed S. Sheteiwy; Jianying Qi; Changqing Chen; Haishui Yang (Science of The Total Environment, 2023)

Biochar reduces bioavailability of phosphorus during swine manure composting: Roles of phoD-harboring bacterial community - Yanan Yin; Chao Yang; Mengtong Li; Sai Yang; Xiaohui Tao; Yucong Zheng; Xiaochang Wang; Rong Chen (Science of The Total Environment, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Eudesmane−type sesquiterpenes from the rhizomes of Atractylodes macrocephala and their bioactivities - Hai-Xin Zhang; Jin-Guang Si; Jing-Rong Li; Meng Yu; Ling-Ling Qin; Chen-Xu Zhao; Tao Zhang; Zhong-Mei Zou (Phytochemistry, 2023)

Four new glycosides from Gerbera piloselloides - Ha Gao; Chen-Xu Zhao; Xin-Yao Luo; Jing-Rong Li; Xiao-Chuan Ye; Tao Zhang; Zhong-Mei Zou (Phytochemistry Letters, 2023)

Effective roxarsone (ROX) and arsenate (As(V)) sequestration from water with magnetic hollow Fe3O4-based Mg/Al layered double hydroxide: Performance and mechanism - Zhipan Wen; Shen Li; Ge Zhang; Runqiao Chen; Yalei Zhang; Xiaoping Liao; Gang Cheng; Rong Chen (Journal of Cleaner Production, 2023)

Soil organic carbon regulates CH4 production through methanogenic evenness and available phosphorus under different straw managements - Zheng-Rong Kan; Zirui Wang; Wei Chen; Ahmad Latif Virk; Feng-Min Li; Jian Liu; Yaguang Xue; Haishui Yang (Journal of Environmental Management, 2023)

The emergence of novel macrolide resistance island in Macrococcus caseolyticus and Staphylococcus aureus of food origin - Feng Zhang; Shi Wu; Jingsha Dai; Jiahui Huang; Jumei Zhang; Miao Zhao; Dongli Rong; Yuanyu Li; Juan Wang; Moutong Chen; Liang Xue; Yu Ding; et al. (International Journal of Food Microbiology, 2023)

Characterization of gallic acid-Chinese yam starch biodegradable film incorporated with chitosan for potential use in pork preservation - Liyuan Rong; Xiaoyao Ji; Mingyue Shen; Xianxiang Chen; Xing Qi; Yulin Li; Jianhua Xie (Food Research International, 2023)

Highly efficient removal of aromatic diamines from the polyurethane bio-hydrolysate by MIL-53 series MOFs - Liyan Chen; Meng Rong; Jiemiao Yu; Qiyu Meng; Shan Ni; Xia Wu; Li Wang; Huifang Xing; Huizhou Liu; Liangrong Yang (Chemical Engineering Journal, 2023)

Rapid, linear, and highly reliable structural-color switching enabled by thermal regulation of chiral nematic mesophases - Dong Li; Rong-Rong Jiang; Si-Kai Chen; Jia-Min Wu; Xiu Dong; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Biochar-assisted anaerobic membrane bioreactor towards high-efficient energy recovery from swine wastewater: Performances and the potential mechanisms - Gaojun Wang; Guohao Liu; Gaofei Yao; Peng Fu; Changxi Sun; Yu Li; Qian Li; Yu-You Li; Rong Chen (Bioresource Technology, 2023)

Carrier type affects anammox community assembly, species interactions and nitrogen conversion - Baoyong Zhang; Nianbo Zhang; Ao He; Chen Wang; Zhen Li; Guanjun Zhang; Rong Xue (Bioresource Technology, 2023)

A glyoxylate-containing benzene derivative and butenolides from a marine algicolous fungus Aspergillus sp. SCSIO 41304 - Xin Qi; Wei-Hao Chen; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Yong-Hong Liu; Jun-Feng Wang; Yong Li (Natural Product Research, 2023)

Remodeled CD146+CD271+ Bone Marrow Mesenchymal Stem Cells from Patients with Polycythemia Vera Exhibit Altered Hematopoietic Supportive Activity - Chao Chen; Mingying Zhang; Rong Li; Jiajia Yuan; Jinqiang Yan; Yuhui Zhang; Wen Xing; Jie Bai; Yuan Zhou (Stem Cell Reviews and Reports, 2023)

Structures of the xyloglucans in the monocotyledon family Araceae (aroids) - Shih-Yi Hsiung; Jing Li; Balazs Imre; Mu-Rong Kao; Hsien-Chun Liao; Damao Wang; Chih-Hui Chen; Pi-Hui Liang; Philip J. Harris; Yves S. Y. Hsieh (Planta, 2023)
Main conclusion The xyloglucans of all aquatic Araceae species examined had unusual structures compared with those of other non-commelinid monocotyledon families previously examined. Abstract The aquatic Araceae species Lemna minor was earlier shown to have xyloglucans with a different structure from the fucogalactoxyloglucans of other non-commelinid monocotyledons. We investigated 26 Araceae species (including L. minor ), from five of the seven subfamilies. All seven aquatic species examined had xyloglucans that were unusual in having one or two of three features: < 77% XXXG core motif [ L. minor (Lemnoideae) and Orontium aquaticum (Orontioideae)]; no fucosylation [ L. minor (Lemnoideae), Cryptocoryne aponogetonifolia , and Lagenandra ovata (Aroideae, Rheophytes clade)]; and > 14% oligosaccharide units with S or D side chains [ Spirodela polyrhiza and Landoltia punctata (Lemnoideae) and Pistia stratiotes (Aroideae, Dracunculus clade)]. Orontioideae and Lemnoideae are the two most basal subfamilies, with all species being aquatic, and Aroideae is the most derived. Two terrestrial species [ Dieffenbachia seguine and Spathicarpa hastifolia (Aroideae, Zantedeschia clade)] also had xyloglucans without fucose indicating this feature was not unique to aquatic species.

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Coexistence of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and IgA nephropathy - Qi Xiong; Wei Lin; Chanjuan Shen; Ting Meng; Rong Tang; Joshua D. Ooi; Peter J. Eggenhuizen; Jinbiao Chen; Wannian Nie; Xia Li; Qiaoling Zhou; Ping Xiao; et al. (Immunologic Research, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

Combined effect of Cu- and ZnO- NPs on antibiotic resistance genes in an estuarine water - Yu-ru Chen; Rong-rong Sha; Xiao-li Sun; Xing-pan Guo; Yi Yang (Frontiers in Marine Science, 2023)
Most studies of whether and how nanoparticles (NPs) affect antibiotic resistance genes (ARGs) focus on testing single NPs type. In this study, we determined the combined effect of Cu- and ZnO- NPs in the water samples collected from the Yangtze River Estuary and found the effect differs greatly from that produced by individual NPs. The results showed that the Cu- and ZnO- NPs co-exposure resulted in an enrichment of ARGs, whereas individual Cu- and ZnO- NPs exposure decreased the abundance of ARGs. Furthermore, the co-exposure of Cu- and ZnO- NPs induced obvious changes in the microbial communities compared to the control communities. Redundancy analysis suggested that the microbial community contributed the most (43.5%) to the ARG profiles, followed by dissolved metal ions (25.7%), MRGs, (19.4%), and MGEs (4.4%). Network analysis found several potential hosts (such as Mycobacterium and Escherichia coli ) and implied the extent of the risk of ARG transmission into various environmental niches by these common microbes.

Insights into the accumulation, distribution and toxicity of pyrene associated with microplastics in rice (Oryza sativa L.) seedlings - Lili Tian; Li Ya Ma; Xiaolong Chen; Jing Ge; Yini Ma; Rong Ji; Xiangyang Yu (Chemosphere, 2023)

Nondestructive and rapid method for sex identification of the tropical sea cucumber Holothuria scabra by anal swab sampling - Zixuan E; Chuhang Cheng; Feifei Wu; Chunhua Ren; Rong Chen; Yingzhu Rao; Bo Ma; Xiao Jiang; Peng Luo; Xiaomin Li; Xin Zhang; Fajun Jiang; et al. (Aquaculture, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Multicopper oxidases GbAO and GbSKS are involved in the Verticillium dahliae resistance in Gossypium barbadense - Fei Wang; Tianxin Lu; Liping Zhu; Aiping Cao; Shuangquan Xie; Xifeng Chen; Haitao Shen; Quanliang Xie; Rong Li; Jianbo Zhu; Xiang Jin; Hongbin Li (Journal of Plant Physiology, 2023)

Strengthen the purification of eutrophic water and improve the characteristics of sediment by functional ecological floating bed suspended calcium peroxide and sponge iron jointly - Zheng Zhu; Yi Wang; Xue-Yi Han; Wen-Huai Wang; Hao-Min Li; Zi-Qi Yue; Wei Chen; Fu-Rong Xue (Journal of Environmental Management, 2023)

Mo isotopes archive oceanic sediments in post-orogenic lithospheric mantle - Feng Huang; Jie Li; Jifeng Xu; Jianlin Chen; Baodi Wang; Pan Hu; Rong Xu; Yunchuan Zeng; Le Zhang; Ting Zhou (Geochimica et Cosmochimica Acta, 2023)

Combining a novel biofilm reactor with a constructed wetland for rural, decentralized wastewater treatment - Rui Zhang; Xianchang Liu; Lutian Wang; Pan Xu; Kai Li; Xiaoxiao Chen; Rong Meng; Yuewu Pu; Xuetong Yang; Diederik P.L. Rousseau; Stijn W.H. Van Hulle (Chemical Engineering Journal, 2023)

Evolving a high-performance bio-imaging tool derived from a compact fluorophore as well as creating a reaction-based fluorescent probe for precise determination of Ag+ - Zi Yi Xu; Xiao Hu Wang; Sha Li Huang; Jing Rong Chen; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2023)

A thin LiGa alloy layer from in-situ electroreduction to suppress anode dendrite formation in lithium-sulfur pouch cell - Rong Li; Liwen Yang; Lei Song; Changan Zhou; Jiayu Zhou; Ting Chen; Chen Wu; Yujia Zeng; Kui Ma; Hairong Yue (Chemical Engineering Journal, 2023)

Poly(ionic liquid) boosts overall performance of electrocatalytic reduction of low concentration of CO gas - Guo-Yi Duan; Xiao-Qiang Li; Jun-Wu Chen; Guang-Rong Ding; Peng-Xin Guan; Bao-Hua Xu (Chemical Engineering Journal, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)